Mitochondrial Respiration Defects in Single-Ventricle Congenital Heart Disease - Xu, Xinxiu; Lin, Jiuann-Huey Ivy; Bais, Abha S.; Reynolds, Michael John; Tan, Tuantuan; Gabriel, George C.; Kondos, Zoie; Liu, Xiaoqin; Shiva, Sruti S.; Lo, Cecilia W. (Frontiers in Cardiovascular Medicine, 2021)
Background: Congenital heart defects (CHD) with single ventricle (SV) physiology is now survivable with a 3-stage surgical course ending with Fontan palliation. However, 10-year transplant-free survival remains at 39-50%, with ventricular dysfunction progressing to heart failure (HF) being a common sequela. For SV-CHD patients who develop HF, undergoing the surgical course would not be helpful, and could even be detrimental. As HF risk cannot be predicted and metabolic defects have been observed in Ohia SV-CHD mice, we hypothesized respiratory defects in peripheral blood mononuclear cells (PBMCs) may allow HF risk stratification in SV-CHD. Methods: SV-CHD (n=20), biventricular CHD (BV-CHD; n=16), or healthy control subjects (n=22) were recruited, and PBMC oxygen consumption rate (OCR) was measured using the Seahorse Analyzer. Respiration was similarly measured in Ohia mouse heart tissue. Results:. Post-Fontan SV-CHD patients with HF showed higher maximal respiratory capacity (p=0.004) and respiratory reserve (p<0.0001), parameters important for cell stress adaptation, while the opposite was found for those without HF (reserve p=0.037; maximal p=0.05). This was observed in comparisons to BV-CHD or healthy controls. However, respiration did not differ between SV patients pre vs. post-Fontan or between pre or post-Fontan SV-CHD patients vs. BV-CHD. Reminiscent of these findings, heart tissue from Ohia mice with SV-CHD also showed higher OCR, while those without CHD showed lower OCR. Conclusion: Elevated mitochondrial respiration in PBMC is correlated with HF in post-Fontan SV-CHD, suggesting PBMC respiration may have utility for prognosticating HF risk in SV-CHD. Whether elevated respiration may reflect maladaptation to altered hemodynamics in SV-CHD warrants further investigation.